Global Trends and Hotspots in Esketamine Research: A Bibliometric Analysis of Past and Estimation of Future Trends - Li X; Xiang P; Liang J; Deng Y; Du J (Dove Medical Press, 2022)
Xiang Li,1 Ping Xiang,2 Jianfen Liang,1 Yifan Deng,1 Jingyi Du1 1Department of Anesthesiology, The Third Affiliated Hospital, Sun Yat-Sen University, Guangzhou, 510630, People's Republic of China; 2Department of Medical Quality Management, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People's Republic of ChinaCorrespondence: Xiang Li, Department of Anesthesiology, The Third Affiliated Hospital, Sun Yat-Sen University, Guangzhou, 510630, People's Republic of China, Tel +86-20-85253132, Fax +86-20-85252297, Email lixiang27@mail.sysu.edu.cnBackground: Being the S-enantiomer of racemic ketamine, esketamine is found to be effective for sedation, analgesia, and treating depression. However, there is no comprehensive bibliometric analysis about esketamine research. In this study, we aimed to determine the scientific output and emerging topics related to esketamine.Methods: Esketamine-related articles and reviews that published between 2000 and 2020 were obtained from the Web of Science Core Collection database, using key word search of "esketamine" "esketamine hydrochloride", "s-ketamine", "S(+)-ketamine", "(S)-ketamine", or "(-)-ketamine". Various bibliographic elements were collected, including the annual number of publications, citation frequency, countries/regions, institutions, authors, journals, and keywords. Two sorts of scientometric software, namely VOS viewer and CiteSpace, were used to conduct bibliometric and knowledge-map analyses.Results: A total of 683 publications were included in the current study. We found the number of publications in esketamine research field had increased annually since 2016. The United States was the leader in this field, with the highest publications number (162, 23.72%), total citations (3504/9713, 36.08%) and H-index (40). The most productive institution was Chiba University in Japan, and esketamine-related papers were mainly published in the journal Anesthesia & Analgesia. The keyword co-occurrence analysis showed that keywords relevant to depression were the most frequent. Moreover, all identified keywords could be divided into four clusters, with the research focus gradually shifting from cluster of "anesthesia and analgesia detection" to "depression treatment effect.".Conclusion: The past two decades have shown a marked increase in esketamine research. The United States maintained a top position worldwide, making the most significant contributions in the field of esketamine research. The contributions and collaborations of Asian countries have continuously increased and is a strong area of growth as well as development in recent years. Additionally, the emerging hotspots of esketamine research concentrate on clarifying its depression treatment effect.Keywords: ketamine, esketamine, bibliometrics, research trends, depression